Modified Mediterranean diet and survival: EPIC-elderly prospective cohort study. Issue 7498 (8th April 2005) - Trichopoulou, Antonia; Orfanos, Philippos; Norat, Teresa; Bueno-de-Mesquita, Bas; Ocké, Marga C; Peeters, Petra HM; van der Schouw, Yvonne T; Boeing, Heiner; Hoffmann, Kurt; Boffetta, Paolo; Nagel, Gabriele; Masala, Giovanna; et al.
Abstract: Objective To examine whether adherence to the modified Mediterranean diet, in which unsaturates were substituted for monounsaturates, is associated with longer life expectancy among elderly Europeans. Design Multicentre, prospective cohort study. Setting Nine European countries (Denmark, France, Germany, Greece, Italy, the Netherlands, Spain, Sweden, United Kingdom). Participants 74 607 men and women, aged 60 or more, without coronary heart disease, stroke, or cancer at enrolment and with complete information about dietary intake and potentially confounding variables. Main outcome measures Extent of adherence to a modified Mediterranean diet using a scoring system on a 10 point scale, and death from any cause by time of occurrence, modelled through Cox regression. Results An increase in the modified Mediterranean diet score was associated with lower overall mortality, a two unit increment corresponding to a statistically significant reduction of 8% (95% confidence interval 3% to 12%). No statistically significant evidence of heterogeneity was found among countries in the association of the score with overall mortality even though the association was stronger in Greece and Spain. When dietary exposures were calibrated across countries, the reduction in mortality was 7% (1% to 12%). Conclusion The Mediterranean diet, modified so as to apply across Europe, was associated with increased survival among older people.